Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7cp01776f
|View full text |Cite
|
Sign up to set email alerts
|

Defect induced ferromagnetism in MgO and its exceptional enhancement upon thermal annealing: a case of transformation of various defect states

Abstract: MgO particles of few micron size are synthesized through a sol-gel method at different annealing temperatures such as 600 °C (MgO-600), 800 °C (MgO-800) and 1000 °C (MgO-1000). EDX and ICP-AES studies confirmed a near total purity of the sample with respect to paramagnetic metal ion impurities. Magnetic measurements showed a low temperature weak ferromagnetic ordering with a T (Curie temperature) around 65 K (±5 K). Unexpectedly, the saturation magnetization (M) was found to be increased with increasing anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Figure showed the room temperature recorded EPR spectrum of Na 2 Sm 2 Ca 6 (PO 4 ) 6 F 2 which showed a resonance signal for Lande g factor(g)= 2.046.Similar kind of resonance signal was also observed very recently in Apatite‐Type (Ba,Sr) 5 (PO4) 3 Br matrix and it was attributed to oxygen vacancy. We have also observed similar resonance signal for oxygen vacancy with g value close to the present samples . In a oxide based matrices the oxygen vacancies can exist in different charged states such as i) neutral i. e. V O 0 , which is formed when two electrons are trapped in doubly charged oxygen vacancy, ii) singly charged oxygen vacancy i. e. V O + .…”
Section: Resultssupporting
confidence: 85%
“…Figure showed the room temperature recorded EPR spectrum of Na 2 Sm 2 Ca 6 (PO 4 ) 6 F 2 which showed a resonance signal for Lande g factor(g)= 2.046.Similar kind of resonance signal was also observed very recently in Apatite‐Type (Ba,Sr) 5 (PO4) 3 Br matrix and it was attributed to oxygen vacancy. We have also observed similar resonance signal for oxygen vacancy with g value close to the present samples . In a oxide based matrices the oxygen vacancies can exist in different charged states such as i) neutral i. e. V O 0 , which is formed when two electrons are trapped in doubly charged oxygen vacancy, ii) singly charged oxygen vacancy i. e. V O + .…”
Section: Resultssupporting
confidence: 85%
“…27 Thus, NEXAFS investigations were extended to angle-dependent measurements in the present study. [28][29][30] In recent years, MgO has attracted more interest due to its unusual magnetism [31][32][33][34] and optical behavior. [35][36][37] This material is also known for phenomena like spin-dependent electron reection, 38 multilevel switching characteristics, 39 and broadband laser emission.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have observed that although oxygen vacancies make MgO optically active, these vacancies have an opposite effect on the magnetism. In 2017 Pathak et al [27] performed some positron annihilation lifetime measurements which indicate the presence of divacancy (2V Mg + 2V O ) cluster along with Mg vacancies at the low annealing temperature. An EPR study showed that MgO compound possesses both singly negative charged Mg vacancies and singly positively charged oxygen vacancies and the spins of both of these vacancies are ferromagnetically coupled.…”
mentioning
confidence: 99%